Early nuclear power plant retirement and policy choices in the New York electricity market - Muhammad Maladoh Bah; Hannes Weigt (University of Basel, Center of Business and Economics (WWZ), 2025)
The U.S. nuclear industry has overcome a challenging period during which low wholesale market prices threatened the survival of nuclear power plants (NPPs). From 2017 to 2019, several U.S. states initiated out-of-market support schemes to bolster the financial conditions of NPPs. This paper provides a comparative cost assessment between the preservation of three upstate New York NPPs under the zero-emission credit (ZEC) support scheme or an early retirement. In addition, the paper explores future market development scenarios with a carbon price mechanism. A bespoke costminimization dispatch model is developed for the New York electricity market along with four neighboring electricity markets. The comparative cost assessment of a nuclear phaseout and ZEC expenditures is not definitive. Results indicate that phasing out upstate NPPs in 2018 and 2021 incurred a slightly higher cost burden for New York consumers compared to the total ZEC expenditures. In contrast, phasing out upstate NPPs in 2030 incurs a lower cost burden compared to the total ZEC expenditure, mainly due to a high credit price. Furthermore, results show that a low carbon price of 51/ton would raise average NYISO prices by 24.1/MWh, thereby improving the long-term income conditions of NPPs, and ensuring sufficient accumulation of nuclear decommissioning funds. The study provides policymakers with a sequence of optimal policy options taking into account the pace of renewable development.
Keywords: L94; Q41; Q48; 330; nuclear power plant; ZEC; New York; electricity market; carbon price